Integration vs marginalization Shaping the patterns of circular migration - Gorodetska, Galyna (Socio.hu Társadalomtudományi Szemle, 2014)
In recent times, the win–win outcomes of circular migration for all the involved stakeholders have come under a thorough academic focus and have increased in social–political importance for both the host and home countries, not to mention the migrants themselves. Given the inherent importance of the issue for countries’ public policies, it comes as no surprise that attention is often paid to the intrinsic pros and cons for both host and home societies. What might ponder, however, is the fact that the main actors of this process, the circular migrants, gain rather limited attention or scrutiny. The main aim of this article is therefore to unveil what actually happens with circular immigrants in the host countries, and which pattern – integration or marginalization – shapes their destiny in the host society. This question will be investigated through a case study of Ukrainian immigrants in Spain. The outcomes of this applied research into the sociology of the circular migration demonstrate that both concepts are not mutually exclusive, and do not fundamentally preclude integration. Key words circular migration, integration, marginalization